The clinical perspective of circular RNAs in neurodegenerative diseases: potential diagnostic tools and therapeutic targets - Li, Xin’ai; Wang, Peng; Qi, Shuo; Zhou, Jingwei; Amalraj, Jeremiah; Wang, Junhui; Ding, Zhiguo (Frontiers in Cellular Neuroscience, 2024)
Neurodegenerative diseases (NDDs) mostly occur in older demographics. With the average lifespan increasing over time, NDDs are becoming one of the major adverse factors affecting human health and the quality of life. Currently, there are no specific diagnostic methods for NDDs and they are usually diagnosed based on nonspecific clinical symptoms and occasionally by biomarkers, such as β-amyloid (Aβ) for Alzheimer’s Disease (AD) and a-synuclein (α-syn) for Parkinson’s disease, etc. However, it is usually too late for most treatment to startr when the aforementioned criteria become detectable. Circular RNAs (circRNAs) are a type of single-stranded, covalently closed, non-coding RNAs that lack a 5' cap structure and 3' terminal poly-A tail. According to recent research, circRNAs may play a crucial role for the onset and progression of some NDDs. These small RNAs may be potential diagnostic and prognostic markers and therapeutic targets for these diseases. This review will provide a comprehensive overview of the recent advancements of knowledge on the functions and the possible underlying mechanism of circRNAs in the pathogenesis and treatment of NDDs.